2013
DOI: 10.3389/fphys.2013.00132
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the influence of vitamin D deficiency on cigarette smoke-induced emphysema

Abstract: Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality worldwide. While the primary risk factor for COPD is cigarette smoke exposure, vitamin D deficiency has been epidemiologically implicated as a factor in the progressive development of COPD-associated emphysema. Because of difficulties inherent to studies involving multiple risk factors in the progression of COPD in humans, we developed a murine model in which to study the separate and combined effects of vitamin D deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 54 publications
5
16
0
Order By: Relevance
“…It is well known that cigarette smoke exposure could result in COPD and emphysema in animals [28][29][30]. Consistent with these reports, we have also previously reported that cigarette smoke-exposed rats developed COPD/emphysema characterized by enlarged alveoli (increased mean linear intersection) [27].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It is well known that cigarette smoke exposure could result in COPD and emphysema in animals [28][29][30]. Consistent with these reports, we have also previously reported that cigarette smoke-exposed rats developed COPD/emphysema characterized by enlarged alveoli (increased mean linear intersection) [27].…”
Section: Discussionsupporting
confidence: 79%
“…In the current study, however, cigarette smoke exposure was used to prepare PAH model in rats. Cigarette smoke exposure resulted in not only COPD/emphysema, which has been previously reported by us and other investigators [27][28][29][30], but also pulmonary arteriolar wall remodeling and PAH as demonstrated in the current study. Specifically, here, we report that cigarette smoke lead to increase of mean pulmonary arterial pressure (mPAP), right ventricular hypertrophy index (RVHI), arterial wall thickness (WT%) and wall area (WA%).…”
Section: Discussionsupporting
confidence: 70%
“…In support of our observations, Sasaki and colleagues showed that female C57BL/6 mice have increased end-expiratory lung volume after 20 weeks of cigarette smoke exposure [16]. Furthermore, total lung capacity was increased in mice exposed to 16 weeks of smoke exposure compared to wild type mice [17]. On the other hand, it is by no means certain that the pathology of smoke exposure in mice will precisely recapitulate that seen in humans.…”
Section: Discussionsupporting
confidence: 73%
“…Measures of lung compliance and elastance are usually similar in C57BL/6 wild type (WT) mice exposed to air or CS for 6 months due to the relatively mild emphysema that develops when this strain is exposed to CS (10) (10) , in CS-exposed C57BL/6 strain gene-targeted mice that have a more severe emphysema type than C57BL/6 WT mice (13) , or in CS-exposed mice subjected to environmental changes that render them more susceptible to the effects of CS (14) . This protocol uses a small animal ventilator to measure reductions in the elastic recoil of the lung (increases in quasistatic lung compliance [Cst] and reductions in tissue elastance [H]), PV flow loops, and changes in airway and tissue resistance in anesthetized mice (15,16) .…”
Section: Pulmonary Function Test (Pfts)mentioning
confidence: 99%